2022
DOI: 10.1002/ctd2.113
|View full text |Cite
|
Sign up to set email alerts
|

The secreted protein augurin is a novel modulator of canonical Wnt signalling involved in osteoblast differentiation

Abstract: The secreted protein augurin is a novel inhibitor of canonical Wnt signalling • Inactivation of the gene encoding augurin (Ecrg4) produced increased osteogenic differentiation of mouse calvarial osteoblasts • Genome-wide association studies showed that an intronic ECRG4 variant (rs66989638) is associated with height and osteoarthritis • Augurin is a new potential drug target to modulate Wnt signalling

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…We have recently shown that Ecrg4 expression is strongly increased during the process of osteoblast differentiation in vitro and that osteoblasts from Ecrg4 −/− mice have an accelerated differentiation, which indicates a role for augurin in osteoblast differentiation [ 37 ].…”
Section: Functionsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have recently shown that Ecrg4 expression is strongly increased during the process of osteoblast differentiation in vitro and that osteoblasts from Ecrg4 −/− mice have an accelerated differentiation, which indicates a role for augurin in osteoblast differentiation [ 37 ].…”
Section: Functionsmentioning
confidence: 99%
“…The suppression of GSK-3β activity leads to β-catenin accumulation into the cytoplasm and translocation to the nucleus, where it interacts with the TCF/LEF transcription factors to activate the transcription of their target genes (right panel). Augurin specifically represses the canonical Wnt/β-catenin signaling pathway, however through which receptor it exerts its action and the precise mechanisms of Wnt signaling repression remain to be unveiled [ 37 ] …”
Section: Signal Transductionmentioning
confidence: 99%
See 3 more Smart Citations